The Digital and non-digital educational media for stunting prevention among children : a scoping review: intervention digital and non digital educational media for stunting prevention among children under five - Kusuma, Inggar Ratna; Pangesti , Wilis Dwi; Agung, Rendi Marta; wibowo, Much Ilham Novalisa Aji Wibowo; Safitri, Mutiara Dien (LPPM Universitas Prima Nusantara Bukittinggi, 2025)
Background: The prevalence of stunting in Indonesia reached 21.5 percent in 2023. Effective and accessible educational strategies are crucial for prevention interventions. With the advancement of technology, both digital and non-digital media have become essential tools for disseminating health information. Objective: This study aims to map and identify the types, characteristics, and effectiveness of digital and non-digital educational media that have been used in stunting prevention programs . Method: This study utilized a scoping review approach following the framework outlined by Arksey and O’Malley, in accordance with the JBI guidelines. Literature searches were conducted across five major electronic databases—PubMed, ScienceDirect, Cochrane Library, Taylor & Francis, and Google Scholar using keywords related to “stunting,” “education,” “digital media,” “non-digital media,” Inclusion criteria consisted of studies focusing on educational media interventions for stunting prevention among children. Extracted data included media type, target audience, intervention design, geographical context, and reported outcomes. Results: Out of 849 identified articles, 10 met the inclusion and exclusion criteria. The analysis revealed four main themes: (1) digital media for pregnancy monitoring, (2) digital media for parental education of children (3) non-digital media for maternal education during pregnancy, and (4) digital media for parental education of children. Conclusion: Non-digital media ensure deeper understanding and cultural relevance, whereas digital media enhance reach and message reinforcement. The effective integration of both digital and non-digital media is essential to develop comprehensive and sustainable stunting prevention programs .